2014
DOI: 10.3390/cells3020627
|View full text |Cite
|
Sign up to set email alerts
|

The Ufm1 Cascade

Abstract: The ubiquitin-fold modifier 1 (Ufm1) is a posttranslational modifier that belongs to the ubiquitin-like protein (UBL) family. Ufm1 is present in nearly all eukaryotic organisms, with the exception of fungi. It resembles ubiquitin in its ability to be ligated to other proteins, as well as in the mechanism of ligation. While the Ufm1 cascade has been implicated in endoplasmic reticulum functions and cell cycle control, its biological role still remains poorly understood. In this short review, we summarize the cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(82 citation statements)
references
References 39 publications
1
81
0
Order By: Relevance
“…On the contrary, the efflux of accumulated cholesterol in macrophages is mediated by the cholesterol reverse transporter family, including SR-BI, ABCA1, and ABCG1 41,42) . Therefore, we delineated the mechanism of UFM1 to attenuate lipid accumulation by examining the alterations results are consistent with a previous report that UFM1 is expressed in various tissues and cell lines and that UFM1 is linked with the acti vation of the ER stress response in atherosclerosis, ischemic heart injury, and T2D 21,48,49) . Taken together, our findings strongly indicate that UFM1 is upregulated in ma crophages under atherosclerotic conditions, both in vivo and in vitro and that UFM1 may be a potential therapeutic target for atherosclerosis.…”
Section: Ufm1 Upregulates Abca1 and Abcg1 Expression But Not Class A supporting
confidence: 59%
See 1 more Smart Citation
“…On the contrary, the efflux of accumulated cholesterol in macrophages is mediated by the cholesterol reverse transporter family, including SR-BI, ABCA1, and ABCG1 41,42) . Therefore, we delineated the mechanism of UFM1 to attenuate lipid accumulation by examining the alterations results are consistent with a previous report that UFM1 is expressed in various tissues and cell lines and that UFM1 is linked with the acti vation of the ER stress response in atherosclerosis, ischemic heart injury, and T2D 21,48,49) . Taken together, our findings strongly indicate that UFM1 is upregulated in ma crophages under atherosclerotic conditions, both in vivo and in vitro and that UFM1 may be a potential therapeutic target for atherosclerosis.…”
Section: Ufm1 Upregulates Abca1 and Abcg1 Expression But Not Class A supporting
confidence: 59%
“…These data indicate diverse functions of UFM1 depending on the function of the target protein. At present, there are increasing evidences, which show that UFM1 is upregulated in pathological conditions that are associated with the activation of the ER stress response, such as type diabetes, ischemic heart injury, and cardiovascular diseases [20][21][22] . Moreover, ER stress is a key regulator of macrophage differentiation and cholesterol deposition in the development of atherosclerosis 23) .…”
Section: Introductionmentioning
confidence: 99%
“…41 Although the precise function has not been elucidated yet, the UFM1 cascade seems to be involved in cellular homeostasis, influencing cell division, growth and endoplasmatic reticulum function. 42 UFM1 is highly expressed in the pancreatic islets of Langerhans and has a role in the development of type 2 diabetes. Another study showed possible involvement in the development of ischemic heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…The conjugation and deconjugation of target proteins by Ubls modulates their function and thereby the regulation of cellular processes. [10] In the Ufm1 modification pathway, Ufm1 is activated by either UFSP1 or UFSP2 to expose a C-terminal glycine residue. [7] Activated Ufm1 then reacts with Uba5 (E1-like enzyme) and is transferred to Ufc1 (E2-like enzyme) before being transferred to its target protein by Ufl1 (E3-like enzyme).…”
Section: Discussionmentioning
confidence: 99%